Alternative food networks: sustainable business models for anti-consumption food cultures. Issue 8 (6th August 2018) - De Bernardi, Paola; Tirabeni, Lia
Abstract : Purpose: The purpose of this paper is to analyse a sustainable business model (SBM) implemented by an Alternative Food Network (AFN), namely the Italian Food Assembly, with the goal of exploring its drivers of success and explaining how it can contribute to enhance sustainable and anti-consumption behaviours. This research aims at combining principles from both SBM innovation and user-driven anti-consumption and well-being habits, in order to develop more successful, comprehensive and community-centred sustainable value propositions. Design/methodology/approach: Given the research goal, an exploratory case study was prepared where multiple sources of data were employed, namely in-depth interviews, participant observation, focus groups and document analysis. Findings: In the light of the Bocken et al. (2014) framework, this paper provides evidence on the implementation of an AFN where it is possible to observe a strong sharing of knowledge regarding sustainable consumption behaviours and an effective dissemination of best practices between members. The authors developed four propositions that support the creation of a sustainable food supply chain, laying the foundation for spreading consumer behaviours and motivations so that they become more sustainable in their consumption habits. Research limitations/implications: Even though the case study is very rich in the amount of data gathered, it cannot be generalised. Further research will overcome this limitation by adding more cases within a comparative approach and through a quantitative methodology. Originality/value: It adds value to recent literature and practice by focussing on how networks of producers, consumers and other actors could act to improve food anti-consumption behaviours, by embodying alternatives to conventional food systems.